THE TERATOGENIC EFFECT OF DIETHYLENE GLYCOL (DEG) ON FETUS MORPHOLOGY IN WHITE MICE (MUS MUSCULUS L.) - BADRIYYA, ELSA; SRANGENGE, YONETA; SIREGAR, JOYCE ARTHA ROSLINA; A., ALMAHDY (International Journal of Applied Pharmaceutics, 2024)
Objective: Diethylene glycol is listed in the Inventory of Cosmetic Ingredients as a solvent, viscosity controller, and fragrance. Most of diethylene glycol's toxicity is caused by ingesting the contaminated product. This study aims to determine the effect of a teratogen caused by diethylene glycol on mice fetuses. Methods: In this study, 20 mice were used, which were divided into four groups. Diethylene glycol was given with three variations of doses 1662.5, 3325, and 6650 mg/kgBW during the organogenesis period, day 6-15. The effects of teratogens observed were maternal body weight, fetal body weight, and number of fetuses, which were analyzed using one-way ANOVA, as well as morphological and skeletal abnormalities, which were analyzed descriptively. Results: Based on the results of the study, there was a significant difference in the body weight of the mice given diethylene glycol and the control group (p<0.05). There was no significant difference in body weight and the number of fetuses in the control and treatment groups (p>0.05). On the results of fixation of Bouins' solution, defects in the form of hemorrhage, resorption sites, and slow growth were found. At the same time, the results of the fixation of alizarin red solution found defects in the sternal, nasal, caudal, metacarpal, metatarsal, and phalanges bones. Conclusion: The conclusion based on the research is that diethylene glycol has the potential to provide teratogenic effects on mouse fetuses.